2020
DOI: 10.7759/cureus.8982
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Effect on Kinesio Taping on Pain and Gait in Patients With Patellofemoral Pain Syndrome?

Abstract: PFPS, we did demonstrate a significant reduction in pain after the application of Kinesio Tape. These results suggest other variables addressed by the Kinesio Tape may be causing the pain associated with PFPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…However no between group differences was found suggesting that both treatment were equally effective to reduce pain intensity in patellofemoral pain syndrome. The results are supported by various previous studies such as a study by Kellish et al (2020) reported significant effect of kinesio tapping in reducing the pain scores on visual analogue scale in patellofemoral pain syndrome patients (7). Similarly a recent study by Mubarrah and Huma (2021) declared that Mulligan tapping significantly lowered the NPRS scores in patients with anterior knee pain patients (5).…”
Section: Resultssupporting
confidence: 80%
“…However no between group differences was found suggesting that both treatment were equally effective to reduce pain intensity in patellofemoral pain syndrome. The results are supported by various previous studies such as a study by Kellish et al (2020) reported significant effect of kinesio tapping in reducing the pain scores on visual analogue scale in patellofemoral pain syndrome patients (7). Similarly a recent study by Mubarrah and Huma (2021) declared that Mulligan tapping significantly lowered the NPRS scores in patients with anterior knee pain patients (5).…”
Section: Resultssupporting
confidence: 80%
“…Two commonly used taping techniques for PFPS include Kinesio Taping ® Method (KT) and Mc-Connell Taping Technique (MT). The MT uses rigid and highly adhesive tape that is structurally supportive while the KT uses more compliantly adhesive taping that can stretch to 130-140% of its original length allowing for enough range of motion [4,5]. MT is thought to correct patellar malalignment and facilitate vastus medialis oblique (VMO) contractions, thereby reducing pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…MT is thought to correct patellar malalignment and facilitate vastus medialis oblique (VMO) contractions, thereby reducing pain [6]. On the other hand, KT is theorized to increase proprioception, improve vascular flow, [7] and help restore proper joint alignment [5]. Due to its low cost and wide availability, patellar taping has been frequently applied in clinical practice either as a sole treatment or as part of a treatment program.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Therefore, many clinicians and physical therapists apply patellar taping to stabilize the patellar malalignment in such cases. 9,10 Previous studies have used various patellar taping techniques, such as kinesio taping and McConnell taping to stabilize the patella in patients with PFPS, [10][11][12][13][14][15][16][17][18][19][20] which is debatable regarding the outcomes in terms of patellar alignment, patellar maltracking, and quadriceps muscle balance. However, to date, insu cient studies have investigated functional outcomes in terms of quadriceps muscle strength and reaction time, and patient-reported outcomes [including the visual analogue scale (VAS) and the Kujala anterior knee pain scale (AKPS)], in PFPS patients with patellar maltracking who applied taping.…”
Section: Introductionmentioning
confidence: 99%